Quand la non-activation des règles devient la règle : regard de géographe sur un problème public qui s’éternise. Le cas de la déprivatisation des rives lacustres (Annecy, Léman) - Alice Nikolli (VertigO)
The theoretical framework of public problem remains quite discreet in geography, even though it is very classical in sociology and political science. Yet it seems useful to analyse conflictual situations regarding space, its sharing and its planning, as well as their (non-)resolution by public policies. The paper proposes to build on this framework to study a problem lasting for over a century: the deprivatization of the shores of Lake Geneva (Switzerland/France) and Lake Annecy (France). The paper reconstitutes the slow and difficult construction of the public problem and then analyses the strategies used to activate or circumvent the existing political rules. Drawing on this case study, we emphasize on the non-linearity of the construction and resolution of the problem and invite to shift the focus on the multiple retroactions between the early (framing, publicization) and late (agenda setting, public policies) stages of the classical model.